The law, the researcher, and occupational health - Jean-Baptiste Fassier (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
The primary role of law in society is to protect people, ensure a common good, settle disagreements, and persuade people to do the right thing. In the field of occupational health and safety (OHS), employees should be guaranteed a safe place to work by law, protecting them from occupational hazards, accidents, and disease. However, it is estimated that 2.3 million workers die annually for reasons attributed to work, mainly due to work-related diseases (1). As important as this number appears, it is likely to be a considerable underestimate of the true number of deaths due to shortcomings in the available data (2). This gap inevitably brings into question the effectiveness of OHS legislation, the process in which it is formulated, and the extent to which it is enforced. The current issue of the Scandinavian Journal of Work, Environment & Health contains a systematic review by MacEachen and colleagues of the qualitative literature on OHS legislation and regulatory enforcement planning and implementation (3). This meta-ethnographic synthesis of 18 qualitative studies yielded four important themes pertaining to regulation formation, regulation challenges, inspector organization, and worker representation, and its findings will certainly reach a large audience among the OHS community. Although the review was conducted with explicit methodological standards, some caveats are worth mentioning. First, the evidence base of the review is limited to a few developed countries (with the notable exception of the Philippines) dominated by Australia and Canada where half of the studies were conducted. The way OHS is regulated in different nation states may vary to a certain extent (4), and, consequently, MacEachen et al's results should be interpreted according to one's own context. Second, half of the studies were published between 1991-2009, before the financial crisis in the US sparked the global recession in the years 2008-2009. Two articles in the review linked weakened OHS legislation coverage to unions being constrained by economic conditions. It is plausible that the general economic decline observed in developed countries has amplified OHS regulation challenges, such as organizational restructuring, complex contracts, and psychosocial issues in the workplace. Third, the findings of the review remain essentially descriptive. They offer insights into policy-making and implementation challenges but stay cautiously away from political science theoretical frameworks, which could be advanced to discuss causal mechanisms linking policy and politics, for example. How to conceptualize the relationship between policy and politics is central to political science. The linkage between policy types (distributive, redistributive, regulatory) and sectors (housing, employment, labor, etc), on the one hand, and politics (forms and strategies of policy-making such as relabeling issues, agenda setting or policy coalitions), on the other hand, is characterized by complex relationships and a certain degree of conflict or consensus for which different theories have tried to account (5, 6). Such theoretical perspectives in political science are somehow missing in the synthesis of MacEachen and colleagues, either due to the content of the studies synthetized, the review process, or both. The development of regulations and associated challenges described in the review fall within the realm of public policy analysis that seeks to explain how decision-makers, elected politicians, interest groups, lobbyists, experts, and political institutions produce public actions intended to have a large-scale impact. The study of public policy emerged in the 1960s at a time where optimism affected the social sciences and nurtured the belief that research could contribute to the success of public action. This overtly confident view was let down by the failure of many state-run programs, to the point that understanding policy failures has been described as intellectually stimulating albeit politically depressing (7). Public policy evaluation faces theoretical, methodological, and political challenges. From a theoretical point of view, political science encompasses a variety of approaches, each one claiming to explain why policies differ between sectors and countries, and why some policies are stable and others change. Methodological challenges pertain to the difficulty in applying experimental approaches to expose the relationships between variables within a political system. Last but not least, political challenges are the limited culture of evaluation in politics and the scarcity of available data to perform evaluations. The lack of accuracy and comparability of statistical tools at the European Union and Member States level to monitor the progress of the European strategy on health and safety at work has been mentioned as a key challenge, in particular with regard to occupational diseases (8). At first sight, some findings of the review could induce a defeatist view of the state's ability to address in a timely manner OHS issues associated with new forms of work in fast-evolving economies, such as outsourcing, temporary work, and international supply chains. In the current era of globalization where influential ideologies advocate for minimal state intervention in economic and social affairs, these findings are concerning. However, other findings open promising research avenues. The influence of the coordination and clarity of communication between parties on OHS should be further explored. The impact of the workers' representative involvement (experts with technical expertise or worksite-based workers with local legitimacy) should also be examined. The optimal degree of precision of OHS laws is still to be determined so that they can be followed and evaluated. The role of employers as policy recipients is largely ignored and the conditions that motivate them to participate in OHS systems should be studied. About a hundred years ago, the German sociologist Max Weber emphasized the radical difference between "Science as a Vocation" and "Politics as a Vocation" (9). Researchers are definitely not supposed to paint the world according to their own views. For the worker's sake, let us hope they can help policy-makers develop laws to change it.